The Influence of Organizational Commitment and Job Stress On Turnover Intention Mediated by Job Satisfaction to Employees PT Federal International Finance (Fifgroup) Ambon Branch - Zulkarnain Sahlan; Novalien Carolina Lewaherilla; F. Leuhery; Gerrit M Pentury (Sean Institute, 2026)
This study aims to analyze the influence of organizational commitment and job stress on turnover intention with job satisfaction as a mediating variable among employees of PT Federal International Finance (FIFGROUP) Ambon Branch. The research method used is a quantitative approach with data collection techniques through distributing questionnaires to employees. The sample in this study was determined using a specific sampling t echnique according to population characteristics. The data analysis technique used was path analysis and mediation test. The results of the study showed that organizational commitment had no effect on turnover intention, while job stress had a positive and significant effect on turnover intention. In addition, organizational commitment and job stress also had a significant effect on job satisfaction. Job satisfaction was proven to act as a mediating variable that strengthens the influence of organizational commitment and job stress on turnover intention. The conclusion of this study is that increasing organizational commitment and job satisfaction as well as good job stress management can reduce the level of employee turnover intention. Therefore, companies are expected to create a conducive work environment to increase job satisfaction and retain employees.